TRANSPARANSI INFORMASI PELAYANAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN SITUBONDO - Rahmad Hidayat; Hadi Wijono; Farida Hanum (ACTON, 2018)
This study aimed to determine the Service Information Transparency in Department of Investment and One-Stop Integrated Services (DPMPTSP) of Situbondo Regency. The research method of this research was qualitative method. This research carried out descriptively in order to know and to describe the reality of the event. The data analysis had been done respectively starting with examining all available data from various sources; from interviews, from observations that had been written in field notes, from documents an drawing conclusions. The results of the study concluded that the transparency of information on business permit services in Department of Investment and Integrated One-Stop Services (DPMPTSP) of Situbondo Regency was not yet transparent in providing services to the customers. This could be seen from the management of public service that had not been published. The costs and time of service had not been transparent. The responsibilities were low such as discipline in terms of service time, promises that had not been fulfilled to customers. The service standards had not been published in the office rooms because the room was not adequate to serve the customers.